Factor structure and psychometric properties of the Arabic Brief COPE among Arab adolescents in the Klang Valley, Malaysia - Sherif, Yosra; Azman, Ahmad Zaid Fattah; Alimuddin, Aishah Siddiqah; Awang, Hamidin; Mohammadzadeh, Marjan (Khyber Medical University, 2025)
Objective: To examine the factor structure and internal reliability concerning the factors of Brief COPE (Coping Orientation to Problems Experienced) for assessing coping skills among Arab adolescents in Malaysia. Methods: A total of 150 eligible Arab migrant adolescents (aged 14 to 18) from the Klang Valley in Malaysia who had experienced depression, anxiety and stress participated in this cross-sectional study from May to July 2022. The factor structure concerning the translated items was investigated utilising the exploratory factor analysis (EFA). Internal consistency reliability was evaluated using Cronbach's alpha coefficients. Moreover, parallel analysis was performed to count the number of components precisely. Results: The Arabic version of Brief COPE demonstrated acceptable psychometric properties. Exploratory factor analysis (EFA) confirmed its suitability for factor extraction (KMO = 0.79; Bartlett's Test, p < 0.0001). A four- factor structure was identified, with all 28 items loading well into the model, explaining 52.3% of the total variance. Factor loadings ranged from 0.52 to 0.77, indicating strong construct validity. Internal consistency was satisfactory, with Cronbach's alpha ranging from 0.74 to 0.88. Conclusion: This research confirms the validity and reliability of the Arabic version of the Brief COPE for usage with Arab migrants and it has the potential as a valid and reliable instrument for future use in assessing coping strategies among minority teenagers.